The SES-CD Could Be a Predictor of Short- and Long-Term Mucosal Healing After Exclusive Enteral Nutrition in Pediatric Crohn’s Disease Patients - Tang, Wenjuan; Hu, Wenhui; Shi, Peng; Ye, Ziqing; Wu, Jie; Zhang, Ye; Wang, Yuhuan; Huang, Ying (Frontiers in Pediatrics, 2022)
Aims To explore the predictors of mucosal healing (MH) for short- and long-term after exclusive enteral nutrition (EEN) in pediatric Crohn’s disease (CD) patients. Methods A retrospective analysis was performed for newly diagnosed active CD patients admitted to our center from January 2017 to 30 December 2020, who were treated with EEN for induction therapy with a minimum of 12 months of follow-up post-EEN. According to the simple endoscopic score for CD (SES-CD), at 1-year post-EEN, 17 patients with an SES-CD < 3 were classified into the sustained MH group (sMH), and 33 patients with an SES-CD ≥ 3 were classified into the sustained non-MH group (sNMH). Statistical methods were used to compare the differences between the two groups and explore the predictors of MH at the end of EEN and 1-year post-EEN. Results The SES-CD in the sMH group was lower than that in the sNMH group both at baseline and the end of EEN [sMH vs. sNMH: 8.7 ± 1.2 vs. 16.2 ± 1.0, respectively, p < 0.001 at baseline; 1.0 (3.5) vs. 4.0 (2.0), respectively, p < 0.01 at the end of EEN]. The weighted Pediatric Crohn’s Disease Activity Index and erythrocyte sedimentation rate in the sMH group were lower than those in the sNMH group at baseline (both p < 0.05), but showed no difference at the end of EEN. From baseline to 1-year post-EEN, compared with patients in the sNMH group, there were more patients classified with L1 in the sMH group at each time point (all p < 0.001) and fewer patients classified with L3 in the sMH group at baseline and 1-year post-EEN. After EEN, fewer patients received infliximab and had a longer exposure time to infliximab in the sMH group than in the sNMH group. Only the SES-CD at baseline was negatively associated with MH at the end of EEN (OR = 1.40 95% CI = 1.12–1.67, p = 0.00) and 1-year post-EEN (OR = 1.33, 95% CI = 1.12–1.58, p = 0.001), and the cut off value was 11.5. Conclusion The SES-CD could predict both short- and long-term MH for EEN. Patients with an SES-CD < 11.5 had a high probability of reaching MH by EEN-inducing therapy and maintaining sustained MH at 1-year post-EEN. Patients with an SES-CD greater than 11.5 at baseline should be treated more aggressively with biologics.